Preparation method of anti-oxidation graphene coated copper composite conductive paste
By using solid carbon sources to grow graphene in a vacuum environment to cover copper powder, the problem of complex and oxidation of copper -guided plasma processing process is solved, and graphene graphene with high antioxidity and excellent conductive performance is achieved. Preparation.
Patent Information
- Application Number
- CN202411516027.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing copper conductive paste preparation methods are complex in technology and are easily oxidized, resulting in insufficient conductivity and oxidation resistance, which limits its wide application.
Using solid carbon sources to directly grow graphene in a vacuum environment and coating copper powder, high-quality graphene-coated copper composite powder is prepared, which is used to prepare anti-oxidation graphene-coated copper composite conductive slurry.
The high oxidation resistance and excellent conductive properties of the conductive slurry are achieved. The process is simple and the cost is low, which is conducive to large-scale production and application.
Abstract
Description
Technical Field
[0001] The invention relates to the field of copper conductive paste, and in particular to a method for preparing an oxidation-resistant graphene-coated copper composite conductive paste. Background Art
[0002] The key part of conductive paste is conductive filler, and the commonly used conductive filler is silver powder. Silver conductive paste made of silver powder has good conductivity, but silver is expensive as a precious metal, and the aggregation of silver particles will cause the paste stability to deteriorate. This makes silver conductive paste subject to great restrictions in the field of low-cost large-scale preparation. The resistivity of copper is second only to that of silver, and using copper powder as a conductive filler can greatly reduce costs, so copper conductive paste can be developed to replace silver conductive paste.
[0003] However, the use of copper powder to prepare copper conductive paste faces the problem of easy oxidation of copper powder. Currently, the common method of silver plating on the surface of copper powder or extremely complicated copper powder treatment is used to improve the antioxidant properties of the conductive paste. This not only increases the cost, but also limits the widespread application of copper conductive paste.
[0004] As a new material composed of carbon atoms, graphene has a stable structure, excellent antioxidant properties, extremely low resistivity, and good electrical conductivity. The preparation of graphene-coated copper composite conductive slurry has good development prospects. The existing preparation technology of graphene / copper conductive slurry often uses graphene powder or redox graphene to directly mix with copper powder, so that the graphene is coated with copper powder. The graphene-coated copper composite powder obtained by this method often faces the problems of uneven mixing and dispersion and easy agglomeration of graphene, which makes the composite incomplete and affects the electrical conductivity and antioxidant properties of the graphene-coated copper composite conductive slurry. Patent 117620187A discloses a method for in-situ growth of graphene. The graphene grown by this method can achieve good coating with copper powder, but multiple gases such as inert gas and reducing gas are needed in the process of graphene growth. The operation process is complicated, which increases the production cost and is difficult to achieve large-scale production and preparation. Compared with the above method, the method of directly growing graphene using a solid carbon source under a vacuum environment can not only achieve a close compounding of graphene and copper powder, but also the prepared graphene-coated copper composite conductive paste has excellent oxidation resistance and conductivity, a simple preparation process and low cost, which is conducive to large-scale production and application. Therefore, it is of great significance to develop a method for preparing graphene / copper composite powder under a vacuum environment and then preparing a highly antioxidant graphene-coated copper composite conductive paste. Summary of the invention
[0005] The present invention provides a method for preparing an oxidation-resistant graphene-coated copper composite conductive paste, so as to solve the problems of complex process and easy oxidation of the conductive paste in the prior art copper conductive paste preparation method, and obtain a conductive paste with excellent conductivity and stability.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing an oxidation-resistant graphene-coated copper composite conductive slurry comprises the following steps: Step 1, preparing organic-coated copper powder; Step 2: using the organic matter in the organic-coated copper powder obtained in step 1 as a solid carbon source, growing graphene on the surface of the copper powder under a vacuum environment, thereby obtaining a graphene-coated copper composite powder; Step 3: mix the dispersant, curing agent and defoaming agent required for preparing the conductive paste and grind them to obtain a mixture, and use the graphene-coated copper composite powder obtained in step 2 as the conductive filler of the conductive paste, add the conductive filler to the mixture in batches and grind them again to obtain the graphene-coated copper composite conductive paste.
[0007] Furthermore, in step 1, the oxide on the surface of the copper powder is first removed, and an organic substance is added to a solvent to form a dispersion of the organic substance; then, the copper powder is added to the dispersion of the organic substance and mixed and stirred for 1 to 12 hours, and after the stirring is completed, centrifugation and drying are performed in sequence to obtain copper powder coated with the organic substance.
[0008] Furthermore, the oxide on the surface of the copper powder is removed by pickling, and the pickled copper powder is then washed and added to the dispersion of the organic matter.
[0009] Furthermore, in step 1, the organic matter is one or more of polymethyl methacrylate, polystyrene, polyvinyl pyrrolidone, stearic acid, rosin, and polyacrylonitrile.
[0010] Furthermore, in step 1, the solvent is one or more of ethanol, ethylene glycol, isopropanol, acetone, carbon tetrachloride, and hexadecanol.
[0011] Furthermore, in step 2, organic matter is used as a solid carbon source, and the copper powder coated with the organic matter is placed in a closed tubular furnace, and the tubular furnace is evacuated to form a vacuum environment, and then the tubular furnace is heated to 650~1050℃ and maintained for 5~30 min for annealing to grow graphene on the surface of the copper powder, thereby obtaining a graphene-coated copper composite powder.
[0012] Furthermore, in the conductive paste of step 3, the mass ratio of the graphene-coated copper composite powder as the conductive filler to the total mass ratio of the conductive paste is 55-85%, and the mass ratio of other components consisting of the dispersant, the curing agent, and the defoaming agent to the total mass ratio of the conductive paste is 15-45%. In addition, the mass ratio of the dispersant, the curing agent, and the defoaming agent in the other components is (1-3): (1-5): (0-3).
[0013] Furthermore, the curing agent is one or more of epoxy resin E-51, epoxy resin E-44, phenolic resin, bisphenol A epoxy resin, cellulose acetate butyrate, and acrylic resin; the dispersant is one or more of triethanolamine, ethylene glycol, ethanol, terpineol, and hexadecanol; and the defoaming agent is one or more of glycerol polyoxyethylene ether, emulsified silicone oil, and polydimethylsiloxane.
[0014] Compared with the prior art, the present invention has the following advantages: (1) Compared with the current main process of directly mixing copper powder with graphene powder, the present invention directly grows graphene on the surface of copper powder under a vacuum environment, and the obtained graphene is coated on the surface of copper powder to obtain a high-quality graphene-coated copper powder composite material.
[0015] (2) The present invention utilizes a solid carbon source to coat copper powder, and graphene-coated copper powder can be obtained by annealing in a vacuum environment. Compared with other processes in which graphene is grown in an atmosphere of hydrogen and methane, the present invention has simpler operation and lower cost, and is conducive to large-scale production.
[0016] (3) The graphene-coated copper composite conductive paste of the present invention has simple ingredients, low cost and good paste stability. The cured paste has excellent oxidation resistance and a resistivity of only 1-1.3×10 -6 Ω·m, has excellent electrical conductivity, and is conducive to large-scale application. DETAILED DESCRIPTION
[0017] The present invention is further described below in conjunction with embodiments.
[0018] This embodiment discloses a method for preparing an oxidation-resistant graphene-coated copper composite conductive paste, comprising the following steps: Step 1: Prepare organic-coated copper powder, the process is as follows: First, the copper powder is pickled to remove oxides on the surface of the copper powder. Specifically, during pickling, the copper powder is added to 10-15 ml of a 0.1%-5% pickling solution, stirred for 30-120 min, allowed to stand after stirring, and then the supernatant is removed to obtain pickled copper powder. After pickling, the copper powder is cleaned by centrifugation for 2-10 times to obtain copper powder with surface oxides removed.
[0019] In this embodiment, the particle size of the copper powder is 1-20 μm; the pickling solution is one or more of hydrochloric acid, sulfuric acid, and nitric acid solution. The solvent used for centrifugal cleaning is one or more of water, ethanol, and ethylene glycol. The centrifuge speed is 2000-5000 r / min, and the centrifugation time is 5-10 min.
[0020] At the same time, the organic matter is added into the solvent so that the organic matter is completely dissolved in the solvent to form a dispersion of the organic matter, so as to facilitate coating of the copper powder.
[0021] In this embodiment, the organic matter is one or more of polymethyl methacrylate, polystyrene, polyvinyl pyrrolidone, stearic acid, rosin, and polyacrylonitrile, and the solvent in the organic dispersion is one or more of ethanol, ethylene glycol, isopropanol, acetone, carbon tetrachloride, and hexadecanol. The volume of the solvent is 10 to 100 ml, and the mass ratio of the organic matter to the copper powder is 1:1 to 10:1.
[0022] Finally, copper powder is added to the organic dispersion and mixed and stirred for 1 to 12 hours to allow the organic matter to fully coat the copper powder. After the stirring is completed, the organic dispersion is centrifuged to remove the supernatant, and then dried to obtain copper powder coated with the organic matter.
[0023] In this embodiment, a centrifuge is used to centrifuge the dispersion of organic matter, the rotation speed during centrifugation is 4000-8000 r / min, the centrifugation time is 5-10 min, the temperature during drying is 50-80° C., and the drying time is 10-120 min.
[0024] Step 2: Using the organic matter in the organic-coated copper powder obtained in step 1 as a solid carbon source, graphene is grown on the surface of the copper powder under a vacuum environment, thereby obtaining a graphene-coated copper composite powder, and the process is as follows: The copper powder coated with organic matter is placed in a closed tube furnace, and a vacuum pump is used to evacuate the tube furnace to form a vacuum environment. Then the vacuum pump is turned off, and the tube furnace is heated to 650~1050 ℃ and maintained for 5~30 min for annealing, thereby growing graphene on the surface of the copper powder with organic matter as a solid carbon source to obtain a graphene-coated copper composite powder.
[0025] Step 3: Mix the dispersant, curing agent and defoaming agent required for preparing the conductive paste and grind them thoroughly to obtain a mixture, and use the graphene-coated copper composite powder obtained in step 2 as the conductive filler of the conductive paste, add the conductive filler to the mixture in batches and grind them again to obtain the graphene-coated copper composite conductive paste.
[0026] In the conductive paste of this embodiment, the mass of the graphene-coated copper composite powder as the conductive filler accounts for 55-85% of the total mass of the conductive paste, and the mass of other components consisting of a dispersant, a curing agent, and a defoaming agent accounts for 15-45% of the total mass of the conductive paste. In addition, the mass ratio of the dispersant, the curing agent, and the defoaming agent in the other components is (1-3): (1-5): (0-3).
[0027] In this embodiment, the curing agent is one or more of epoxy resin E-51, epoxy resin E-44, phenolic resin, bisphenol A epoxy resin, cellulose acetate butyrate, and acrylic resin, the dispersant is one or more of triethanolamine, ethylene glycol, ethanol, pinene alcohol, and hexadecanol, and the defoaming agent is one or more of glycerol polyoxyethylene ether, emulsified silicone oil, and polydimethylsiloxane.
[0028] Finally, the graphene-coated copper composite conductive paste obtained in step 3 is applied on the substrate, and the cured graphene-coated copper composite conductive paste is obtained after the paste is cured.
[0029] The following is a description of the performance test results of the graphene-coated copper composite conductive paste obtained in this embodiment and the cured copper conductive paste. The test results are as follows: (1) Conductive properties: The resistivity of the cured copper conductive paste is 1.9~2.1×10 -6 Ω·m, and the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment is 1~1.2×10 -6 Ω·m, the resistivity is reduced by 47.3% compared with copper conductive paste.
[0030] (2) Antioxidant properties: 2.1) The two cured conductive pastes were placed in a room temperature environment for 120 days respectively. The resistivity of the copper conductive paste increased by 46.5%, while the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment increased by only 8.1%.
[0031] The pickled copper powder and the graphene-coated copper powder were placed in a room temperature environment for 16 days and then the conductive slurry was prepared. After curing, the resistivity of the cured copper conductive slurry increased by 74.1% compared with the copper conductive slurry prepared immediately after pickling, while the resistivity of the cured graphene-coated copper composite conductive slurry obtained in this embodiment increased by only 3.2%.
[0032] 2.2) The two conductive pastes after curing were baked at 100° C. for 3 h on a heating platform. The resistivity of the copper conductive paste increased by 51.4%, while the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment increased by only 4.9%.
[0033] The two types of conductive pastes after curing were baked at 150° C. for 3 h on a heating platform. The resistivity of the copper conductive paste increased by 101%, while the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment increased by only 6.1%.
[0034] The two types of conductive pastes after curing were baked at 200° C. on a heating platform for 3 h, respectively. The resistivity of the copper conductive paste increased by 122%, while the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment increased by only 10.8%.
[0035] 2.3) High humidity environment test: After being placed in an environment of 40% humidity and 60° C. for 3 hours, the resistivity of the copper conductive paste increased by 23.1%, while the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment only increased by 1.4%.
[0036] After being placed in an environment of 60% humidity and 60° C. for 3 hours, the resistivity of the copper conductive paste increased by 27.6%, while the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment only increased by 2.53%.
[0037] After being placed in an environment of 80% humidity and 60° C. for 3 hours, the resistivity of the copper conductive paste increased by 31%, while the resistivity of the cured graphene-coated copper composite conductive paste obtained in this embodiment only increased by 3.25%.
[0038] It can be seen from the above test results that the performance of the cured graphene-coated copper composite conductive paste obtained in this embodiment is significantly better than that of the copper conductive paste.
[0039] The preferred embodiments of the present invention are described in detail above. The embodiments described in the present invention are merely descriptions of the preferred embodiments of the present invention, and are not intended to limit the concept and scope of the present invention. The various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction, and such combinations, as long as they do not violate the concept of the present invention, should also be regarded as the contents disclosed in the present disclosure. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0040] The present invention is not limited to the specific details of the above-mentioned embodiments. Within the technical concept of the present invention and without departing from the design concept of the present invention, various modifications and improvements made to the technical solution of the present invention by technical personnel in this field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have been fully recorded in the claims.
Claims
1. A method for preparing an oxidation-resistant graphene-coated copper composite conductive paste, characterized in that: The following steps are involved: Step 1, preparing organic-coated copper powder; Step 2: using the organic matter in the organic-coated copper powder obtained in step 1 as a solid carbon source, growing graphene on the surface of the copper powder under a vacuum environment, thereby obtaining a graphene-coated copper composite powder; Step 3: mix the dispersant, curing agent and defoaming agent required for preparing the conductive paste and grind them to obtain a mixture, and use the graphene-coated copper composite powder obtained in step 2 as the conductive filler of the conductive paste, add the conductive filler to the mixture in batches and grind them again to obtain the graphene-coated copper composite conductive paste.
2. The method for preparing an oxidation-resistant graphene-coated copper composite conductive paste according to claim 1, characterized in that: In step 1, the oxide on the surface of the copper powder is first removed, and an organic substance is added to a solvent to form a dispersion of the organic substance; then, the copper powder is added to the dispersion of the organic substance and mixed and stirred for 1 to 12 hours. After the stirring is completed, centrifugation and drying are performed in sequence to obtain copper powder coated with the organic substance.
3. The method for preparing an oxidation-resistant graphene-coated copper composite conductive paste according to claim 2, characterized in that: The oxide on the surface of the copper powder is removed by pickling, and the pickled copper powder is then washed and added to a dispersion of organic matter.
4. The method for preparing an oxidation-resistant graphene-coated copper composite conductive paste according to claim 1 or 2, characterized in that: In step 1, the organic matter is one or more of polymethyl methacrylate, polystyrene, polyvinyl pyrrolidone, stearic acid, rosin, and polyacrylonitrile.
5. The method for preparing an oxidation-resistant graphene-coated copper composite conductive paste according to claim 2, characterized in that: In step 1, the solvent is one or more of ethanol, ethylene glycol, isopropanol, acetone, carbon tetrachloride, and hexadecanol.
6. The method for preparing an oxidation-resistant graphene-coated copper composite conductive paste according to claim 1, characterized in that: In step 2, organic matter is used as a solid carbon source, and the copper powder coated with the organic matter is placed in a closed tubular furnace, and the tubular furnace is evacuated to form a vacuum environment in the tubular furnace, and then the tubular furnace is heated to 650~1050°C and maintained for 5~30min for annealing to grow graphene on the surface of the copper powder, thereby obtaining a graphene-coated copper composite powder.
7. The method for preparing an oxidation-resistant graphene-coated copper composite conductive paste according to claim 1, characterized in that: In the conductive paste of step 3, the mass of the graphene-coated copper composite powder as a conductive filler accounts for 55-85% of the total mass of the conductive paste, and the mass of other components consisting of a dispersant, a curing agent, and a defoaming agent accounts for 15-45% of the total mass of the conductive paste. In addition, the mass ratio of the dispersant, the curing agent, and the defoaming agent in the other components is (1-3): (1-5): (0-3).
8. The method for preparing an oxidation-resistant graphene-coated copper composite conductive paste according to claim 1 or 7, characterized in that: The curing agent is one or more of epoxy resin E-51, epoxy resin E-44, phenolic resin, bisphenol A epoxy resin, cellulose acetate butyrate, and acrylic resin; the dispersant is one or more of triethanolamine, ethylene glycol, ethanol, terpineol, and hexadecanol; and the defoaming agent is one or more of glycerol polyoxyethylene ether, emulsified silicone oil, and polydimethylsiloxane.
Citation Information
Patent Citations
Method for preparing graphene / copper composite material by in-situ catalysis of solid carbon source on surfaces of copper powders
CN104874803A
Method for preparing grapheme / copper composite material by loading solid carbon source on copper powder surface in impregnation manner
CN105081312A
Graphene-coated copper nano particle composite conductive ink and preparation method thereof
CN109401443A
High-quality graphene-copper composite material and method for rapidly preparing high-quality graphene-copper composite material based on graphene confinement growth
CN117758101A
Cited By
Conductive slurry and preparation method of antioxidant copper powder in conductive slurry
CN120032941A
Preparation method of sulfur-doped graphene composite copper conductive paste
CN120452928A
Conductive copper paste prepared by combining liquid nonferrous metal with graphene and preparation method of conductive copper paste
CN121355003A